2000
DOI: 10.1177/016146810010200108
|View full text |Cite
|
Sign up to set email alerts
|

Community Colleges and Contract Training: Content, Origins, and Impact

Abstract: Over the last three decades, most community colleges have broadened their economic development role to include contracting with employers to train current or prospective employees in job and academic skills. This article describes the main contours of the community college's involvement in contract training, explains how this involvement arose, and analyzes its impact on the community college. This analysis is based both on national data on the general prevalence and form of contract training and on case studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…While the magnitude of this threat necessarily differs between disciplines, in the social sciences, we found that open communication and discussion about product outcomes and features dispelled these concerns. Furthermore, clarifying role expertise worked to equalize power relations, which, when unchecked, has been shown to negatively affect UICs (Dougherty & Bakia, 2000), while setting realistic expectations at the outstart of the partnership helped mitigate future disagreements about timelines or conflicting expectations (Austin et al, 2021;Locket et al, 2008). As a whole, we found that open, candid, and frequent exchanges were paramount to our collaboration with industry.…”
Section: Discussionmentioning
confidence: 81%
“…While the magnitude of this threat necessarily differs between disciplines, in the social sciences, we found that open communication and discussion about product outcomes and features dispelled these concerns. Furthermore, clarifying role expertise worked to equalize power relations, which, when unchecked, has been shown to negatively affect UICs (Dougherty & Bakia, 2000), while setting realistic expectations at the outstart of the partnership helped mitigate future disagreements about timelines or conflicting expectations (Austin et al, 2021;Locket et al, 2008). As a whole, we found that open, candid, and frequent exchanges were paramount to our collaboration with industry.…”
Section: Discussionmentioning
confidence: 81%
“…Private companies can collaborate with community colleges to design workforce training programs to suit their needs. Moreover, private companies have a voice in determining the curriculum of instruction that is offered to the workers (Dougherty & Bakia, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…"Normal" schools were established with government funding in order for working-class individual to train as teachers, (Franklin 2020). Community-colleges emerged to help satisfy the growing demand for higher education (Allen, 1995), and vocational colleges (Dougherty and Bakia, 2000) can provide specific required industrial training.…”
Section: Research and Teaching And Institutionsmentioning
confidence: 99%